Study of post-operative pulmonary complications in patients of emergency abdominal surgeries - Verma, Siddhartha; Bhardwaj, Ankur; Patil, Sagar Manohar (International Surgery Journal, 2018)
Background: Post-operative Pulmonary Complications (PPCs) form a significant chunk of post-operative morbidity. Their incidence varies from 2.7-23% in multiple studies. Pre-disposing factors can be divided as: pt. related: >60yrs, ASA class≥2 and COPD; procedure related: long surgeries (≥3hrs), emergency surgeries. Till now, most of the studies have focused on elective surgeries. In this study, I have studied morbidity and risk factors of PPCs in emergency abdominal surgeries. Methods: It is a retrospective case control study, carried out in 50 patients in M.B. Government Hospital, Udaipur over 1 year. Cases comprised of those patients who underwent emergency laparotomy and developed PPCs. Controls were selected from group who didn’t develop PPC. Results: Incidence of PPCs in emergency abdominal surgeries was found to be 2.9%. Elderly patients had more chances of developing PPCs. Smoking was found to be twice as common in case group. Those who quit smoking ≥1 year before surgery benefitted the most. Pre-OP chest x-ray abnormalities were 3 times more common in case group. Upper abdomen surgeries were 20% more common in Case group. Surgeries lasting for ≥ 3 hours had increased chances of PPCs. Total hospital stay was 21.7 days in cases (12.5 in control), total ICU stay was 8.5 days (1.4). 28% of the PPCs patients could not be saved. Conclusions: Pre-operative chest examination, cheat x-ray and regular SpO2 monitoring helps in diagnosing PPCs earlier. Early mobilization and deep breathing exercises should be encouraged.